Délivrés sur ordonnance : les voyages vus à travers les journaux de bord des chirurgiens - Odile GANNIER (E-REA)
Captains’ journals were not the only documentary accounts written onboard ship in the 18th century. Officers and even simple sailors also kept records and this paper will examine the perceptions of shipboard surgeons whose texts may be considered as particularly multi-faceted because they provide original insights into the voyaging conditions. Further, surgeons were trained to make observations and had privileged access to the inhabitants as well as to the crew members which also contributed to the uniqueness of these sources.During the Solide’s voyage around the world (1790-1792), Claude Roblet, surgeon, wrote a particularly exhaustive and entertaining account and also kept a “journal de maladies” listing ailments and his pharmaceutical supplies. To his credit, only one man out of the 50 onboard died and Roblet is recognised as having adopted particularly innovative methods for treating scurvy. The journal is not only a fine account of the peoples and places encountered but it also bears detailed witness to the conditions and ambience onboard ship.